Financial statement analysis of Zakat institutions in Kedah and Selangor: year 2015 and year 2016 - Nor Salwani, Badrul Hisham (2018)
Analysis of financial statement in an organization is important for stakeholders to estimate the growth of financial performance and future forecast planning. Then, analyzing the financial statement of zakat institutions such as Lembaga Zakat Negeri Kedah and Lembaga Zakat Selangor is mostly important to estimate the performance of zakat institutions especially in the context of zakat collection and distribution, and related with financial statement such as income statement and balance sheet to assess its sustainability in the future. Outrages community about poor performance of zakat collection and inefficiency of zakat distribution to the asnaf should be answered using detailed analysis towards financial data reported and audited. Hence, the purpose of this study is to analyze the financial statement based on annual reports of zakat institutions in Kedah and Selangor in year 2015 and year 2016 by using analysis percentage of horizontal and vertical analysis between zakat collection and distribution. Another analysis adopted is ratio analysis based on liquidity analysis in terms of working capital, current ratio, and quick ratio. Debt repayment ability analysis uses debts ratio while return on assets is listed under performance analysis. This study found that in general, there was an increase or decrease in zakat collection by category of zakat. Furthermore, the results also found that the total zakat collection was lower compared to zakat distribution as well as the increase or decrease in the pattern of zakat distribution and their ratio analysis. Some suggestions and policy implications are suggested in this study.